Pengaruh User Generated Content (UGC) dan Price Bundling terhadap Keputusan Pembelian Produk Richeese Factory Cabang Cibinong - Annisa Nuur Aulia; Dedi Junaedi; Rio Kartika Supriyatna (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study examines the influence of User Generated Content and Price Bundling on purchasing decisions at Richeese Factory’s Cibinong branch. A quantitative approach was used, with data collected through questionnaires distributed to 109 respondents. Multiple linear regression analysis revealed that both User Generated Content and Price Bundling have a positive and significant effect, both partially and simultaneously, on consumer purchasing decisions. Keywords: User Generated Content, Price Bundling, Purchasing Decision.